New species of the genus Rhodorhipha Laguerre, 2018 (Lepidoptera: Arctiini) from Peruvian Amazon - Grados, Juan (2022)
A new species Rhodorhipha dalyi sp. nov. from Peru (Tambopata river, Madre de Dios, Peru) is described and illustrated. The species is part of a complex of similar species related to R. subflammans (Rothschild). Publicación registrada en Zoobank/ZooBank article registered:LSID urn:lsid:zoobank.org:pub:68DD8A72-8357-417F-A111-C446236B79C3Acto nomenclatural/nomenclatural act:Rhodorhipha dalyi Grados, 2022LSIDurn:lsid:zoobank.org:act:7EC5CC89-9A63-45C0-AD1E-92DC54055131